Soap film of tensioned fabric structure in the form of handkerchief surface / Mohd Haziman Wan Ibrahim and Mohd Nasir Abdul Hadi and Yee Hooi Min - Wan Ibrahim, Mohd Haziman; Yee, Hooi Min; Abdul Hadi, Mohd Nasir (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Form-finding has to be carried out for tensioned fabric structure in order to determine the initial equilibrium shape under prescribed support condition and pre-stress pattern. Tensioned fabric structures are normally designed to be in the form of equal tensioned surface. Tensioned fabric structure is highly suited to be used for realizing the surfaces of complex or new forms. However, the research study on a new form as a tensioned fabric structure has not attracted much attention. Alternative source of inspiration of minimal surface which could be adopted as form for tensioned fabric structure is very crucial. The aim of this study is to investigate initial equilibrium shape of tensioned fabric structures in the form of Handkerchief surface, u=v=0.2 and u=v=1.2. Experimental form-finding using soap film model is frequently used to develop the possible form of uniformly stressed surfaces. Apart from that, soap film model also provides a means for checking the accuracy of computational form-finding results. In this study, soap film model is used to investigate surface form corresponding to boundary shape defined by mathematical equation for minimal surface. Computational form-finding using nonlinear analysis method has been used in this study. The study proposes an alternative architectural surface for architect and structural engineer to consider Handkerchief surface, u=v=0.2 and u=v=1.2 applied in tensioned fabric structure. The results on factors affecting initial equilibrium shape can serve as a reference for proper selection of surface parameter for achieving a structurally viable surface. Such in-sight will lead the improvement of rural basic infrastructure, economic gains, sustainability of built environment and green technology initiative.